Teachers’ Perceptions and Experiences in Integrating Generative AI into Learning: A Phenomenological Inquiry in Indonesian Secondary Schools - Dede Kurniawan (LP. Ma'arif Janggan Magetan, 2026)
The development of Generative Artificial Intelligence (AI) has opened new pedagogical opportunities, yet empirical studies exploring how secondary school teachers in developing countries navigate its ethical and practical tensions remain scarce. This study aims to fill this gap by providing an in-depth understanding of teachers’ perceptions and experiences in adapting Generative AI in Indonesian secondary schools. Employing a qualitative phenomenological approach, this study involved eight teachers utilizing platforms such as ChatGPT, Gemini, and Canva AI. Data collected through in-depth interviews, observations, and document analysis were analyzed using the Miles and Huberman interactive model. The findings reveal a complex paradox: while teachers perceive Generative AI as a powerful creative tool that accelerates lesson planning and time efficiency, they simultaneously experience heightened anxiety regarding student dependency, the erosion of authentic critical thinking, and the blurring of academic integrity. Furthermore, teachers face tensions between the push for digital innovation and the lack of robust institutional ethical guidelines. This study contributes unique theoretical insights by conceptualizing teacher AI adoption not merely as technological acceptance, but as an ongoing ethical negotiation. Practically, the findings urge policymakers to design culturally responsive, ethically grounded AI training programs rather than purely technical workshops, ensuring sustainable human-AI collaboration in education.